Biogeographic and diversity analysis of intertidal seaweeds and associated peracarids in the Northeast Atlantic - Herrero, Javier Jimenez (2020)
The distribution and biodiversity patterns of intertidal seaweeds and associated peracarids were studied along the Northeast Atlantic region from 65ºN to 27ºN of latitude. In order to determine what factors drive the geographical distribution of intertidal communities of seaweeds and peracarids, twenty-seven stations and nine abiotic factors were considered (fetch, air temperature, precipitation, insolation, SST, chlorophyll-a, pH, aragonite saturation, OHI). A total of 12779 specimens were sorted and identified to the species or genus level, of which the vast majority belonged to the group of algae. In order to assess biogeographical groups of these species along the Northeast Atlantic, a CLUSTER analysis as well as a NMDS analysis were carried out, resulting in the identification of three ecoregions; 1)Northern Europe, 2)Central Iberian Peninsula and 3)Southern Macaronesia. CCA and NMDS analyses showed high correlations between environmental factors such as precipitation, insolation and SST minimum albeit to a lesser extent, and species distribution. Macaronesian species were correlated with higher temperature and insolation whereas those of the Iberian peninsula were correlated with higher pH and chlorophyll. On the other hand, the abundance that was similar among all species and the results of the SIMPER analysis indicated a certain homogeneity of species without dominance of one over another. Both the species richness (S) and α diversity (indexes of H’, Dsimp and eH’) presented a decreasing latitudinal gradient towards higher latitudes. An exception to this pattern was observed for β-diversity, probably due to the homogeneity of abundance of species observed between regions, mainly affected by abiotic factors of the local environment. Os padrões biogeográficos variam de acordo com as diferentes zonas do oceano; em águas pouco profundas, a distribuição dos organismos fica mais irregular devido a uma variedade de fatores, como características geológicas, efeitos das marés, mas tambem, foi demonstrado que ...